MOTIF DAN KEPUASAN ANAK MUDA KOTA DENPASAR MENONTON MUKBANG FARIDA NURHAN MELALUI PLATFORM YOUTUBE (E-Jurnal Medium, 2022)
YouTube is defined as one of the social media with features that provide opportunities for users to upload, view, and share videos between users. The term YouTuber is known as a creator of content that will be displayed in the form of videos uploaded on YouTube. One of the Indonesian YouTubers who is famous for Mukbang content is Farida Nurhan. At this writing, the researcher focuses on identifying the motives of young people, especially in Denpasar City when watching Farida Nurhan's Mukbang content, while also identifying the satisfaction of young people in watching the content. The subjects of this research are young people with an age range of 16-30 years in Denpasar City. Denpasar City was chosen as the research location for the reason that Denpasar City is the city with the highest number of internet users in Bali. This study uses the motives of media use by Dennis McQuail, namely, information motives, personal identity motives, social integration and interaction motives, and entertainment motives. The theory applied in this study is the theory of use and satisfaction, and uses descriptive statistical methods with purposive sampling techniques. Data collection was obtained by distributing questionnaires using a Likert scale and literature study. The results of this study indicate that of the four existing motives, there are two motives that are satisfied in watching Farida Nurhan's Mukbang through YouTube, namely the information motive and the entertainment motive. While the motives that are not satisfied are the motives of personal identity and the motives of integration and social interaction. Keywords: Motive, Satisfaction, Farida Nurhan, Mukbang